Algorithms for finely adjusting etch depths to improve the diffraction efficiency uniformity of large-aperture BSG. (20th February 2015) - Wu, Lixiang; Qiu, Keqiang; Liu, Ying; Fu, Shaojun
Abstract: Beam sampling gratings (BSGs) employed in high-power laser systems usually have large aperture so that the adequate uniformity of diffraction efficiency is difficult to obtain. We proposed a deterministic method using controllable non-uniform etch to improve the efficiency uniformity of large-aperture BSGs. During the ion beam etching (IBE) process, etch depths are finely adjusted by the dynamic leaf. The motion trajectory of the dynamic leaf is calculated using the fine adjustment algorithm. Simulations are conducted on the basis of a typical example. The simulation predictions show that the cumulative error is 0.067 nm and about 99.1% of depth differences are in the range of the required etch depth tolerance, which suggests that the diffraction efficiency uniformity of BSG is expected to be effectively improved and thus can meet the requirement of a RMS of 5%. As a cost-effective solution, it also has a broad prospect in many optical fabrication fields, especially for the fabrication of large optics.